Tactile function in children with unilateral cerebral palsy compared to typically developing children - Auld, M.; Boyd, Roslyn; Moseley, G.; Ware, R.; Johnston, L. (2012)
Purpose: Tactile deficits have been understudied in children with unilateral cerebral palsy (UCP) using a limited range of tactile assessments. This study aims to characterize performance across a comprehensive battery of tactile registration and perception assessments in children with UCP and typically developing children (TDC). Methods: Fifty-two children with UCP (Gross Motor Function Classification System I = 34, II = 18; Manual Ability Classification System I = 36, II = 16) and 34 TDC were assessed using Semmes Weinstein Monofilaments (tactile registration), and single-point localization, double simultaneous, static and moving two-point discrimination, stereognosis, and texture perception (tactile perception). Results: Children with UCP performed consistently worse with their impaired hand than their unimpaired hand (Z = 2.77-5.61; p < 0.005). Both hands of children with UCP performed worse than either hand of TDC (Z = -2.08 to 5.23; p = 0.037-< 0.001). Forty percent of children with UCP had tactile registration and perception deficits, 37% had perception deficits only and 23% had no tactile deficit. The larger the tactile registration deficit, the poorer the performance on all tactile perceptual tests (r = 0.568-0.670; p = < 0.001). Conclusions: Most children with UCP demonstrate poor tactile perception and over one-third also demonstrate poor tactile registration. We contend that tactile dysfunction may contribute to functional impairment and is a possible target for intervention. © 2012 Informa UK, Ltd.